African christianity: a living and vibrant repository of christian faith – Part I - Thachuparamban, Johny (Fronteiras - Revista de Teologia da Unicap, 2018)
Africa continent has played a remarkable role in the formation and growth of Christian faith and culture, right from its infancy to its present state. While much has been written on the topic of Christianity in Africa, relatively little attempt has been made in acknowledging it as one of the pillars of faith in Christendom, a status attributed exclusively to the West and the East. Hence, this article aims at rectifying this perspective by presenting Africa as a significant, living and vibrant repository of Christian faith. This claim is substantiated by giving an overview of the growth of Christianity in Africa to establish its antiquity. The history is divided into four phases: the beginning of Christianity in North Africa, the decline of the early African Church due to Islam; and the colonization or modern period. The fourth phase, the Africanization of Christianity will be dealt with in the second part of this article.